Conching of dark chocolate – Processing impacts on aroma-active volatiles and viscosity of plastic masses - Guckenbiehl, Yvonne; Morales Romero, Aurora Magdalena; Haug, Helen; Ortner, Eva; Rothkopf, Isabell; Schweiggert-Weisz, Ute; Büttner, Andrea; Gola, Susanne (Current Research in Food Science, 2024)
The conching process plays a key role in determining the sensory and rheological properties of dark chocolate. To further understand this process, changes in the chocolate mass during plastic conching were investigated on a time-resolved basis with varying conching temperature, shear direction, and with or without the presence of residue from previous trials (pre-charge) on the conche vessel wall. Six selected odorants (acetic acid, benzaldehyde, linalool, 2,3,5,6-tetramethylpyrazine, 2-phenylethanol, 2-phenylethyl acetate) were quantified in fat and particle phases of chocolate masses. Particularly at elevated conching temperature, the odorant concentrations were found to decrease (up to 78.0% in the fat phase). The highest concentrations of desired odorants were determined mostly after conching without pre-charge. During conching, odorants were observed to accumulate increasingly in the fat phase (up to 91.7%) with decreasing odorant polarity. Similarly, it was found that conching temperature and the absence of pre-charge had the highest impact on the rheological properties of the chocolate mass, resulting in lowest and highest complex viscosity, respectively. In conclusion, some positive outcomes of conching, namely the retention of desired odorants and the reduction of viscosity, were inversely related at elevated temperature or in the absence of pre-charge, necessitating compromises to achieve optimal flow properties and flavor. Our results contribute to a deeper understanding of the influence of conching on the quality of dark chocolate by providing insights into the complexity of aroma migration and rheological changes during conching.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Aroma distribution; Chocolate flavor; Closed cavity rheometer; Conching parameters; Gas chromatography-mass spectrometry; Plastic conching